A changeable thermal conductivity and optoelectronic-mechanical wave behavior in a microelongated, non-locally rotating semiconductor media - Kamel, Alwaleed; Alhejaili, Weaam; Hassan, Wafaa; El-Bary, Alaa A.; Lotfy, Khaled (Frontiers in Physics, 2023)
In this study, we investigate the effect of a rotation field on a homogeneous photothermoelastic nonlocal material and how its thermal conductivity changes as a result of a linearly distributed thermal load. The thermal conductivity of an interior particle is supposed to increase linearly with temperature. Microelastic, non-local semiconductors are used to model the problem in accordance with optoelectronic procedures, as proposed by the thermoelasticity theory. The micropolar-photothermoelasticity theory takes into account the medium's microelongation properties in accordance with the microelement transport processes. This mathematical model is solved in two dimensions (2D) using harmonic wave analysis. Dimensionless components of displacement, temperature, microelongation, carrier density, and stresses are generated when the non-local semiconductor surface is subjected to the right boundary conditions. For silicon (Si) material, the wave propagation impact of the main physical fields is examined and graphically shown for various values of variable thermal conductivity, thermal relaxation durations, nonlocality, and rotation parameters.